Traditional Ceremony of Buná tribal ‘Don Tomon’ Ritual to Respect the Ancestors’ ‘Bei-gon-gua’ - João da Silva (Green Publisher, 2025)
This study focuses on the Buná tribe’s traditional ceremony, the ‘Don Tomon’ ritual, which honors the ancestors’ ‘Bei-gon-gua’. This phenomenon reflects the customary practices that uphold and honor the cultural heritage imparted by previous generations of Buná throughout their eras, preserving the memory of their creative endeavors for subsequent generations. The method of this research analysis involves a description, interviews, and observation analysis, utilizing both direct and indirect techniques with informants as respondents. This process includes conducting interviews to analyze data after gathering information from five narrators in the field: Púgeben Deu dato of Wetaba village, located in Tilomar of Covalima district. The direct method employs interviews with the informants as respondents to gather essential and relevant information for this research, while indirect techniques involve obtaining supplemental details from narrative sources to fill in any gaps in the historical information of this writing through telephone, Whatapps messages, or mutual feedback. This study aims to compile and unveil the concealed narrative for future generations to follow as a guide to their ancestors from millions of years ago. This study focuses on the Buná tribe's traditional ceremony of the ‘Don Tomon’ ritual, honoring the Ancestors’ ‘Bei-gon-gua’. It explores the phenomenon of traditional practices aimed at honoring and adhering to cultural legacies passed down by previous generations of Buná throughout their eras, in memory of the creative careers they bequeathed to their descendants. The ritual ceremony called as ‘Don Tomon’, grilling the hand to respect the ancestors of Buná ‘Bei gon gua’, the cultural heritage of Buná through their pathways.